THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, LEARNING MOTIVATION, AND UTILIZATION OF LEARNING RESOURCES MATHEMATICS LEARNING OUTCOMES OF EIGHTH GRADE STUDENTS - Siti Nurfauziah; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2018)
Results of low mathematics associated with many factors. Numerical ability, learning motivation, and utilization of learning resources are several factors that allegedly associated with students’ mathematics study learning outcomes. This research aims to determine whether or not a positive and significant relationship between Numerical Ability, Learning Motivation, and Utilization of Learning Resources with Mathematics Learning Outcomes of Eighth Grade Students Even Semester Muhammadiyah Junior High School 1 Yogyakarta (SMP Muhammadiyah 1 Yogyakarta) in Academic Year 2016/2017. The population used in this research is all of the eighth-grade students, even semester SMP Muhammadiyah 1 Yogyakarta, in the academic year 2016/2017 with the total number of 194 students and divided into seven classes. Sampling class using accidental sampling technique to the class, so that obtained class VIII B. Data collection techniques using test method and the questionnaire method. Test prerequisite analysis using the normality test, independent test, and the linearity test. Analysis of data used linear regression analysis and correlation analysis. The results showed a positive and significant relationship between numerical ability, learning motivation, and utilization of learning resources with mathematics study results with and , too, obtain . Multiple correlation coefficient (R) of with a learn regression equation . Relative contribution of X1 , X2 , and X3 with coefficient of determination was and affective contribution X1 , X2 , and X3 .